Carbon-isotope records of the Early Jurassic (Toarcian) oceanic anoxic event from the Valdorbia (Umbria-Marche Apennines) and Monte Mangart (Julian Alps) sections: palaeoceanographic and stratigraphic implications - Sabatino, N; Neri, R; Bellanca, A; Jenkyns, H; Baudin, F; Parisi, G; Masetti, D (2009)
The Toarcian oceanic anoxic event (ca 183 Ma) coincides with a global perturbation marked by enhanced organic carbon burial and a general decrease in calcium carbonate production, probably triggered by changes in the composition of marine plankton and elevated carbon dioxide levels in the atmosphere. This study is based on high-resolution sampling of two stratigraphic successions, located in Valdorbia (Umbria-Marche Apennines) and Monte Mangart (Julian Alps), Italy, which represent expressions of the Toarcian oceanic anoxic event in deep-water pelagic sediments. These successions are characterized by the occurrence of black shales showing relatively low total organic carbon concentrations (compared with coeval strata in Northern Europe), generally <2% and low hydrogen indices. On this basis, they are similar to other Toarcian black shales described from the Tethyan region. The positive and negative carbon-isotope records from the two localities permit a high-resolution correlation such that ammonite biostratigraphy information from Valdorbia can be transferred to those parts of the Monte Mangart section that lack these fossils. Spectral analyses of δ13Corg values and of CaCO3 percentages from the sedimentary records of both the Valdorbia and Monte Mangart sections reveal a strong cyclic pattern, best interpreted as an eccentricity signal which hence implies a duration of ca 500kyr for the negative carbon-isotope excursion. Based on the carbon-isotope curves obtained, the high-resolution correlation between the Italian successions and a section in Yorkshire (Northern Europe) confirms the supposition that the apparent mismatch between the dating of the Toarcian oceanic anoxic event in the Boreal and Tethyan realms is an artefact of biostratigraphy. © 2009 The Authors. Journal compilation © 2009 International Association of Sedimentologists.